Silicon dioxide based Nano sensor to measure glucose level in blood - Kavitha, Mrs.G.; Kumar, Dr.K.Senthil (International Journal of Engineering and Technology, 2018)
Diabetes is a growing problem affecting many people in the world. Diabetes leads to various complications like lower limb amputations, blindness, cardiovascular disease etc. Diabetes has many complexity that is reduced by individual monitoring and control of glucose level. Glucose level monitoring occur with recent development in Nanotechnology. Nanotechnology develops nanosensors which measure glucose level. Nanosensors fabricated by silicon dioxide in mass production reduces the cost of the nanosensors. Nanosensors made of silicon dioxide read the blood samples of a person without diabetes and a diabetic person with the help of SIGVIEW and analyzed using MATLAB. Statistical analysis is made with comparison of spectrogram, magnitude response, probability distribution, time domain and the autocorrelation of normal blood signals and diabetic signals. Comparison results in separation of a normal and diabetic person with an excellent performance of nanosensors in mass production.